Comparison of the Nutritional Values of Toddler Milks Available in Italy - Riva, Enrica; Verduci, Elvira; Banderali, Giuseppe; Capra, Maria Elena; Giovannini, Marcello (International Journal of Child Health and Nutrition, 2013)
If breast milk is not available infant formula ensures a balanced intake of nutrients and is undoubtedly more suitable for infants than cows’ milk. In particular, it should point out the absolute necessity to postpone to the end of the first year of life, or even after the 2 nd year, the use of cow’s milk for the extreme imbalance of nutrients that lead to high-protein diets and low levels of polyunsaturated fats, iron and zinc. As a consequence, in the absence of breast milk, the use of an appropriately adapted formula in the first year of life and the use of “toddler milk” from 12 to 36 months may represent adequate nutritional alternatives, especially when compare to the use of cow milk, and in particular may appear to play a fundamental role in the prevention of iron deficiency anemia. Different varieties of toddler milk are currently available in Italy. This review outlines the nutritional differences between breast, toddler and cows’ milks, and compares different brands of toddler milk.